Kompensasi Finansial Sebagai Variabel Intervening dalam Kepuasan Kerja Dan Beban Kerja Terhadap Prestasi Kerja Karyawan - Rachmasari, Astri; Irawati, S. Anugrahini (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
The aims of this study is to determine the effect of job satisfaction and workload on employees performance with financial compensation as an intervening variable in car rental companies Sidoarjo. It used quantitative methods,  sampling  methods, and path analysis. The number of samples as 70 employees in car rental company at Sidoarjo. Using the Path analysis, the result showed that the (1) Job satisfaction has a positive and significant effect on financial compensation with a large effect of 0.29 units for every 1 unit increase in financial compensation (2) Work load has an insignificant effect on financial compensation with a big effect of 0.175 units for every 1 unit increase in financial compensation ( 3) Job satisfaction has a positive and significant effect on employee work performance with a large effect of 0.791 units for every 1 unit increase in work performance, (4) Work load has a negative effect on employee work performance with a big effect of 0.83 units for every 1 unit decrease in work performance , (5) Financial compensation has an insignificant effect on employee work performance with a large effect of 0.006 units for every 1 unit increase in work performance. Simultaneously (1) Job satisfaction and workload simultaneously have a positive and significant effect on financial compensation with a value of 12% simultaneously on financial compensation (2) Job satisfaction, workload and financial compensation simultaneously have a positive and significant effect on performance employee work with a simultaneous influence value of 51% on financial compensation. And Path Analysis, (1) Indirectly, the job satisfaction variable has an insignificant effect on employee work performance through financial compensation as an intervening variable so it cannot mediate with an influence value of 0.058 units (2) The workload variable has no significant effect on employee work performance through financial compensation as an intervening variable so it cannot mediate with an influence value of 0.058 units.